Autonomous drone landing pad system with contact charging - Shabaz Hassan (2018)
The Unmanned Aerial Vehicle (UAV) industry has experienced rapid growth in the past few years. However, the Lithium Polymer (LiPo) batteries installed on Unmanned Ground Vehicles has largely remained unchanged, with flight times remaining under 25-30 minutes, limiting the range of drones. In this thesis document, a highly robust and reliable landing pad is proposed, which through its design also allows fast contact-based charging of the drone. This landing pad is meant to be installed on portable Unmanned Ground Vehicles (UGVs) which can travel longer ranges to the target destination, then deploy the UAV only when needed. This saves precious battery time spent on just flying to and from the destination. This dissertation will first explore the exhaustive physics simulations and prototyping phases that we went through to finalize our landing pad shape and design. The shape proposed then lead to the design of a novel configuration of copper contacts, both on the drone and on the landing pad. These contacts align, touch, and allow rapid contact-based balance charging with any drone orientation while nullifying the risk of battery terminal shortage. The landing pad circuitry will then be elaborated, which deals with a circuit that ensures that all 4 terminals of the LiPo battery are connected with the landing pad through our novel copper contacts configuration. Only then do they allow the charging current to flow. It is critical to ensure that once this charging current starts flowing into the batteries, the rotors and circuitry of the UGV remain connected to the battery and must be disconnected so that they do not damage the batteries or charger by drawing current during this delicate charging process. A portable auto-shutoff circuit is thus designed and proposed. Finally, in conclusion, this dissertation depicts going through a successful test run of our project and proposes possible improvements.